2017
DOI: 10.1108/jmtm-11-2016-0154
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supply chain management practices on supply chain and manufacturing firms’ performance

Abstract: Purpose – This paper theorises and develops seven dimensions (strategic supplier partnership, level of information sharing, quality of information sharing, customer service management, internal lean practices, postponement and total quality management) into a SCM practices (SCMPs) construct and studies its causal relationship with the conceptualised constructs of supply chain performance (SCP) and manufacturing firms’ performance (MFP). The study also explores the causal relationship between SCP and MFP. \ud … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 114 publications
(119 reference statements)
7
103
1
2
Order By: Relevance
“…The coefficients of lead time were negative −0.2269 (Table 5, Model 7). These results suggest that customer responsiveness generates better market share and financial performance by shorter order-to-delivery time and faster customer response time [26]. These findings are also aligned with Droge et al [69], who showed that time-to-product and responsiveness benefit ROA and ROS by minimizing the delivery speed and providing customer service.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The coefficients of lead time were negative −0.2269 (Table 5, Model 7). These results suggest that customer responsiveness generates better market share and financial performance by shorter order-to-delivery time and faster customer response time [26]. These findings are also aligned with Droge et al [69], who showed that time-to-product and responsiveness benefit ROA and ROS by minimizing the delivery speed and providing customer service.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies had two shortcomings considering these four operational dimensions (delivery, flexibility, cost, and inventory). First, the measurement of these dimensions was proposed in a set of question items [26]. Although the effects of operational performance on financial performance can be found in these studies, we consider that measurable variables are more suitable rather than subjective feelings in the questionnaire.…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…Effect of SCM practice positive to the SCM performance [6]. Another research by Al-Shboul et al, [11] also confirms that the SC practice brings influences on the SC performance in the manufacturing companies.…”
Section: The Conceptual Research Frameworkmentioning
confidence: 74%
“…The implemented supply chain practice to reach the optimal SC performance needs some integration across internal functions within the company and external parties as suppliers and customers [10]. SC practice is with indicators such as supplier collaboration, flexibility partners, connected and usage of internet, customer focus with satisfaction, lean production system, with internal integration, and quality management system [11]. The SCM practice in retail companies in India as customer relationship management, supplier relationship management, goal congruence, and information sharing [2].…”
Section: Supply Chain Practicementioning
confidence: 99%
See 1 more Smart Citation